Islam and Local Traditions: The Study of the Thinkings of Abdurrahman Wahid (1940-2009) and Khalil Abdul Karim (1930-2002) an Indonesian and an Egyptian Perspective - Siti Mahmudah (Sunan Kalijaga: International Journal of Islamic Civilization, 2018)
Islam and local tradition had already coexisted peacefully since Islam was revealed by Allah for the first time through the Gabriel Angel to the Prophet Muhammad in Mecca on 610 M. According to Mohammed A. Muqtedar Khan, there were traditions and ethics of Islam, based on the origin of the the sharia misunderstood by the most Muslims until now. Abdurrahman Wahid (Gus Dur) with his theory of the Pribumisasi Islam and Khalil Abdul Karim with his theory about the early existence of the Islam and sharia has been revealed among the pre-Islamic Arab tradition as the blueprint for Islam and the sharia in this era. Both of these theories are those of the continuation of Islam for all times and places.  For the first time, Islam and the sharia gave high appreciation and respect to the Arab tradition and had even enshrined Arab traditions that are considered good and maslahat for humanitarian life remains entrenched to the teachings of Islam and enshrined in the Qur'an. Both of these theories can be used as the basis for rejecting the discovery of Timothy Daniel about "Islamic Spectrum in Java" (2009) which holds that the religious practice of Java is the Kejawen belief (a syncretic), because the teachings of Islam has mixed with local traditions. Therefore, I assert that the religious practice of Java is very diverse and cannot be called as a Kejawen belief (a syncretic). The practice of the Kejawen belief in religious practice in Java is a form of Islam whichis a contextual learning and will continue its process on the perfection of Islam to continue to honor the tradition of the Javanese community that has been practiced by their ancestors and has been successively crystallized and is very difficult to eliminate. Some examples are: bathing with flower tradition in the wedding event, laying flowers at the entrance of the house every Friday night, and riyungan. The reason is that the Muslim community is still able to practice the good and maslahat tradition like in the first era ofIslam in Mecca and Madina.